Penerapan Strategi Bauran Pemasaran 7P (Marketing Mix) dalam Meningkatkan Nilai Penjualan - Ningsih, Bekti Widya; Rahmatika, Arivatu Ni'mati; Zakiya, Zakiya (JoEMS (Journal of Education and Management Studies), 2023)
In the current era of developing marketing management science, marketing strategy still dominates in influencing fluctuations in sales and profit values. The lower the costs of production, distribution and consumption, the greater the profit or profit. This research aims to determine the effectiveness of marketing mix strategies in increasing sales value and profits at Dhyhijab Store Jombang. Dhyhijab Store is a business that operates in the women's fashion sector. There are various methods in developing marketing strategies, one of which is the marketing mix strategy. This method is easier to develop and apply because it is right on target in its mix to increase sales income. This research uses the 7P method. The results of the research show that implementing a marketing mix strategy which includes: product, price, promotion, place, people, physical environment and process can improve sales value at Dhyhijab Store Jombang. Positive and negative impacts experienced by Dhyhijab Store in implementing marketing mix strategies. Obstacles faced by Dhyhijab in implementing marketing mix strategies and efforts to overcome these obstacles.